Differential microbial assembly processes and co‐occurrence networks in the soil‐root continuum along an environmental gradient. Issue 2 (5th April 2022) - Zhong, Yangquanwei; Sorensen, Patrick O.; Zhu, Guangyu; Jia, Xiaoyu; Liu, Jin; Shangguan, Zhouping; Wang, Ruiwu; Yan, Weiming
Abstract: Microorganisms of the soil‐root continuum play key roles in ecosystem function. The Loess Plateau is well known for its severe soil erosion and thick loess worldwide, where mean annual precipitation (MAP) and soil nutrients decrease from the southeast to the northwest. However, the relative influence of environmental factors on the microbial community in four microhabitats (bulk soil, rhizosphere, rhizoplane, and endosphere) in the soil‐root continuum along the environmental gradient in the Loess Plateau remains unclear. In this study, we investigated 82 field sites from warm‐temperate to desert grasslands across the Loess Plateau, China, to assess the bacterial diversity, composition, community assembly, and co‐occurrence networks in the soil‐root continuum along an environmental gradient using bacterial 16S recombinant DNA amplicon sequencing. We discovered that the microhabitats explained the largest source of variations in the bacterial diversity and community composition in this region. Environmental factors (e.g., MAP, soil organic carbon, and pH) impacted the soil, rhizosphere, and rhizoplane bacterial communities, but their effects on the bacterial community decreased with increased proximity to roots from the soil to the rhizoplane, and the MAP enlarged the dissimilarity of microbial communities from the rhizosphere and rhizoplane to bulk soil. Additionally, stochastic assembly processes drove the endosphere communities, whereas the soil, rhizosphere, and rhizoplane communities were governed primarily by the variable selection of deterministic processes, which showed increased importance from warm‐temperate to desert grasslands. Moreover, the properties of the microbial networks in the rhizoplane community indicate more stable networks in desert grasslands, likely conferring the resistance of microbial communities in higher stress environments. Collectively, our results showed that the bacterial communities in the soil‐root continuum had different sensitivities and assembly mechanisms along an environmental gradient. These patterns are shaped simultaneously by the intertwined dimensions of proximity to roots and environmental stress change in the Loess Plateau. Abstract : Changes in microbes in the soil‐root continuum along an environmental gradient were investigated. The soil, rhizosphere and rhizoplane communities were governed by deterministic processes. Environmental stress enlarged the dissimilarity of microbial communities in the soil‐root continuum. Root‐associated microbiomes did not destabilize at locations with higher environmental stress. Highlights: Changes in microbes in the soil‐root continuum along an environmental gradient were investigated. The soil, rhizosphere and rhizoplane communities were governed by deterministic processes. Environmental stress enlarged the dissimilarity of microbial communities in the soil‐root continuum. Root‐associated microbiomes did not destabilize at locations with higher environmental stress.